City of Atlanta Brownfields Area-Wide Planning Program - Berry, Seanna; Cotter, Dan; Frackelton, Alexandra; Lee, Susannah; Madden, Mackenzie; McRae, Stephen; Ranney,Ted; Terranova, Patrick; Voyles, Travis (Georgia Institute of Technology, 2012)
Fall 2012 Studio. Prepared by City of Atlanta Office of Planning & Georgia Institute of Technology School of City and Regional Planning in Partnership with Atlanta BeltLine, Inc. & Invest Atlanta, December 31, 2012. The new area-wide approach to brownfield redevelopment highlights barriers and opportunities that extend beyond individual sites. It seeks to catalyze area-wide revitalization through the clean-up and redevelopment of targeted brownfield sites. The implementation strategy takes into account local planning efforts, best practices and goals identified by the communitiy. It brings together partners and resources to leverage the City's existing brownfield assessment and cleanup tools. The plan's brownfield reuse recommendations identify and prioritized five geographic redevelopment nodes within the overall project area: Murphy Triangle, Green Enterprise District, Metropolitan Yards, Crossroads Center, and Fort McPherson Gateway. Each node has a distinct redevelopment strategy that addresses conditions of blight with a particular emphasis on prioritized brownfield sites. Technical advisors and fall 2012 studio instructors: Nancey Green Leigh, Professor; Nathanael Hoelzel, PhD Student.